Registro de charcoal em depósitos do final do cretáceo da Península Antártica: proxy na avaliação do contexto deposicional e paleoambiental - Manfroi, Joseline (Universidade do Vale do Rio dos Sinos, 2014)
The presence of macroscopic charcoal in the fossil record offers the opportunity to a range of assessments on the paleoenvironmental context that gave rise to this type of record. Among their applications are aspects involving in the geological and paleontological studies of recent years, such as changes in oxygen content in the atmosphere and the association of vegetation to pyrogenic contexts. The present study assessed the presence of macroscopic charcoal in deposits of the Late Cretaceous of Antarctic Peninsula, whose genesis in a fore arc tectonic context, resulted in a highly influenced volcanic deposition. Some of the material here studied comes from the collection undertaken in the Antarctic expeditions made in PROANTAR-Brazil, on King George Island and Nelson Island, being stored at the Laboratory of Life and Earth History (LaViGea), at the Vale do Rio dos Sinos University (UNISINOS), and part was courtesy from the Chilean Antarctic Institute (INACH). The samples were analyzed under a stereomicroscope (increases between 10 and 40 times) seeking by the presence of charred wood plant fragments, after mechanically removed from the sediment and analyzed under a Scanning Electron Microscope (SEM). The analysis allowed the definition of morphoanatomical structures that allows determinate the dynamics of paleofires and its effect over the original vegetation. Two sites showed charred remains proper to this analysis, one in southern King George Island (Price Point), the other at the northern sector of the Nelson Island (Rip Point). The analysis shows wood fragments preserving part of its cellular structure and simple transverse, with uniseriate piths, which allow relating the material forms to the gymnosperms cellular structures.The fusion of the cell walls, with clear marks of rupture, indicate high firing temperatures (340°C to 600°C), which associated to the proximal volcanic context informed by the associated lithologies, allows to suggest a heated fallout tephra like the source of ignition and preservation of wood materials.
Keywords: Península Antártica; Cretáceo superior; Paleoincêndios; Carvão vegetal macroscópico; Antarctic Peninsula; Late Cretaceous; Paleofires; Charcoal; ACCNPQ::Ciências Exatas e da Terra::Geologia